2019
DOI: 10.1186/s12864-018-5409-z
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing identifies common pathways between cigarette smoke exposure and replicative senescence in human airway epithelia

Abstract: BackgroundAging is affected by genetic and environmental factors, and cigarette smoking is strongly associated with accumulation of senescent cells. In this study, we wanted to identify genes that may potentially be beneficial for cell survival in response to cigarette smoke and thereby may contribute to development of cellular senescence.ResultsPrimary human bronchial epithelial cells from five healthy donors were cultured, treated with or without 1.5% cigarette smoke extract (CSE) for 24 h or were passaged i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Transcriptome changes in senescent cells induced by RS and cigarette smoke exposure also indicate that NF-κB is related to aging [ 93 ]. Cigarette smoke exposure and RS are well-known senescence inducers [ 94 ].…”
Section: Omics 1 Transcriptome Regulation Of Nf-κb and Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptome changes in senescent cells induced by RS and cigarette smoke exposure also indicate that NF-κB is related to aging [ 93 ]. Cigarette smoke exposure and RS are well-known senescence inducers [ 94 ].…”
Section: Omics 1 Transcriptome Regulation Of Nf-κb and Agingmentioning
confidence: 99%
“…Cigarette smoke exposure and RS are well-known senescence inducers [ 94 ]. Voic et al [ 93 ] performed RNA-seq in passaged cigarette smoke extract (CSE)-exposed and non-CSE-exposed senescent primary human bronchial epithelial cells and showed that GSEA indicated dysfunction in the regulation of ROS, proteasome degradation, and NF-κB signaling under either RS or CSE. miRNA analysis has also been conducted to explore the influence of aging.…”
Section: Omics 1 Transcriptome Regulation Of Nf-κb and Agingmentioning
confidence: 99%
“…• * ROS signaling [26,39,40] • * NFκB signaling [47] • * p21 pathway [16,[28][29][30] • * Endoplasmic reticulum (ER) stress [48] • * SA-βgal activity [24,26,[35][36][37][38] Therapy-induced senescence * AREG, * CXCL8, * IL1A, * IL-1B, * IL-6, * IL8 * MMP2, * MMP3, * PAI-1, * SPINK1, * t-PA, and WNT16B…”
Section: Overview Of Cellular Senescence 21 Definitionmentioning
confidence: 99%
“…A recent study utilizing RNA sequencing approaches in CSE exposure and senescent conditions in airway epithelial cells demonstrated that CS and senescence conditions induce common signaling responses, including genes that regulate ROS, proteasome degradation, and NF-κB signaling [47]. Voic and colleagues report 243 common gene expression changes in epithelial cells when exposed to CSE or induced senescence [47].…”
Section: Contribution Of Cs To Cellular Senescencementioning
confidence: 99%
See 1 more Smart Citation